Flipped classroom methodology: perception of students of different university degrees - Cristina Mendaña-Cuervo; Raquel Poy-Castro; Enrique López-González (Universidad de Málaga, 2019)
This study provides evidence on the perception of students belonging to different Degrees about the relationship between the Flipped Classroom methodology and the improvement of attitudinal and motivational aspects, and the skills acquired with its implementation. The opinion of the students (before and after the implementation of the methodology) has been collected using an ad hoc questionnaire. Responses from students in different contexts have been considered in order to be able to generalize the results, given the interdisciplinarity of the sample. The results positively endorse the experience, especially in the perception of the competences acquired. However, in relation to the attitudinal and motivational aspects, they are not conclusive.